Biomechanical analysis of rotation strategy of backward somersault in artistic gymnastics - Miyazaki, S.; Fujii, N. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to examine the rotation strategy used by gymnasts to successfully land after a backward somersault. Nine male university gymnasts (1.66 +/- 0.03 m, 61.2 +/- 0.75 kg) performed a backward-tucked somersault from a box (0.3 m height). Three-dimensional coordinate data was collected by a Vicon MX+ system. We compared the trials in which the landing succeeded and trials in which the landing failed. There was a difference in the moment of inertia during the airborne phase and the phase time. The results of this study suggest that changing the moment of inertia during the airborne phase has a significant effect on the body rotation. In particular, it is considered that the timing at which the phase is switched by changing the moment of inertia determined the body rotation.